Comment on “Confucian thought of “Harmony between Man and Nature” and contemporary society construction” - Li, Yuanxu (2024)
Commented article: LIU, Yanling; Wu, Yan. Confucian thought of “harmony between man and nature” and contemporary society construction. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 4, “Eastern thought”, e0240068, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14666.